2021
DOI: 10.1007/s40629-020-00160-4
|View full text |Cite
|
Sign up to set email alerts
|

Severe allergic reactions after COVID-19 vaccination with the Pfizer/BioNTech vaccine in Great Britain and USA

Abstract: SummaryTwo employees of the National Health Service (NHS) in England developed severe allergic reactions following administration of BNT162b2 vaccine against COVID-19 (coronavirus disease 2019). The British SmPC for the BNT162b2 vaccine already includes reference to a contraindication for use in individuals who have had an allergic reaction to the vaccine or any of its components. As a precautionary measure, the Medicines and Healthcare products Regulatory Agency (MHRA) has issued interim guidance to the NHS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
17

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 13 publications
0
34
0
17
Order By: Relevance
“…It needs to be emphasized, however, that the study patients with a history of allergy and/or anaphylaxis who demonstrated good vaccine tolerance constituted a group of individuals who had been qualified for vaccination following guidelines and recommendations prerequiring stratification and phenotyping of such patients [22,23]. Patients with a history of anaphylaxis to vaccines and injection drugs containing polyethylene glycol (PEG), as potentially susceptible to hypersensitivity reactions to the PEG component of vaccines [24][25][26], had undergone allergological consultations recommended by the Polish Allergological Society prior to being vaccinated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…It needs to be emphasized, however, that the study patients with a history of allergy and/or anaphylaxis who demonstrated good vaccine tolerance constituted a group of individuals who had been qualified for vaccination following guidelines and recommendations prerequiring stratification and phenotyping of such patients [22,23]. Patients with a history of anaphylaxis to vaccines and injection drugs containing polyethylene glycol (PEG), as potentially susceptible to hypersensitivity reactions to the PEG component of vaccines [24][25][26], had undergone allergological consultations recommended by the Polish Allergological Society prior to being vaccinated [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Das U.S. National Institute of Allergy and Infectious Diseases (NIAID) hat gemeinsam mit der US-amerikanischen Food and Drug Administration (FDA) eine Studie initiiert, die Reaktionen auf beide COVID-19-Impfstoffe untersuchen soll in Abhängigkeit von zuvor vorhandenen anti-PEG-Antikörpern [1,3].…”
Section: Immunmechanismen Der Anaphylaxien Auf Die Covid-19-impfstoffeunclassified
“…Kreuzreaktivität zwischen PEGs und ihren Derivaten, d. h. strukturell verwandten Polymeren wie Polysorbaten, besteht aufgrund gemeinsamer Moleküleinheiten [21]. PEGs galten lange Zeit als biologisch inert, aber immer mehr Hinweise deuten darauf hin, dass sie es nicht sind, und verschiedene anti-PEG-Antikörper wurden bei bis zu 72 % einer Population gefunden [1,3], vermutlich als Folge der Exposition gegenüber Kosmetika und Arzneimitteln.…”
Section: Immunmechanismen Der Anaphylaxien Auf Die Covid-19-impfstoffeunclassified
See 2 more Smart Citations